Characterizing antiseizure medication in patients with diagnosis of epilepsy in San Jose Infantil and San Jose Centro Hospitals: A retrospective cohort study in Colombia, 2019-2022 - Jean Paul Vergara; Karen Lorena Horta Garavito; Gregory Corena Demarchi; Valentina Galvis Palomino (Acta Neurológica Colombiana)
Introduction: Epilepsy is one of the most common neurological diseases in the world that affects millions of people. We aimed to characterize antiseizure medications (ASM) and to evaluate their clinical behavior in terms of treatment adherence and seizure control of patients treated for epilepsy in two hospitals in Bogotá, Colombia: San José Centro and San José Infantil, between 2019 and 2022.